Regional Integration and Natural Resources Who Benefits? Evidence from MENA - Carrère, Céline (The World Bank, 2012)
This paper builds on theoretical predictions that show that gains from regional integration are unevenly distributed between resource rich and poor countries. It explores the effects of different integration schemes in the Middle East and North Africa. The results suggest that within the Pan Arab Free Trade Agreement, there is significant trade creation for resource poor countries associated with regional integration, and no evidence of trade diversion. In resource rich countries, however, there is evidence of pure trade diversion in both resource-rich/labor-abundant countries and resource-rich/labor-importing countries. This underscores the idea that regional integration can help to spread the benefits of unevenly distributed resource wealth among the region's economies